In children with Hashimoto’s thyroiditis the evolution over time of thyroid status may differ according to the different presentation patterns - Zirilli, Giuseppina; Velletri, Maria Rosa; Porcaro, Federica; Candela, Gilberto; Maisano, Pina; La Monica, Giuseppina (Acta Biomedica Atenei Parmensis, 2015)
Aim: to report the salient literature news concerning the relationships between thyroid function presenting patterns and subsequent biochemical evolution of Hashimoto’s thyroiditis (HT) in pediatric age. Design: the most recent reports from pediatric literature concerning biochemical thyroid function patterns at HT presentation and their spontaneous changes over time were analyzed and shortly commented. Results: from the analysis of pediatric literature on this theme, it emerges that HT in children may present with a very heterogeneous biochemical picture ranging from overt hypothyroidism to overt hyperthyroidism. The presenting biochemical pattern may also condition its subsequent evolution over time. Conclusions: a) the most common biochemical pattern at HT diagnosis in children is euthyroidism, followed by overt hypothyroidism, subclinical hypothyroidism (SH) and hyperthyroidism; b) the association with HT negatively affects the evolution over time of SH; c) in the cases with either Turner syndrome or Down syndrome the evolution over time of SH is more severe than in those without these chromosomopathies.